Increasing Prevalence of Hypertension in Bangladesh: A review (Cardiovascular Journal, 2015)
Hypertension is a major public health problem globally in both the developed and developing countries. In Bangladesh, approximately 20% of adult and 4065% of elderly people suffer from hypertension. According to Non Communicable Disease risk factors survey, one third of the Bangladeshi population never measured their blood pressure. The prevalence of self reported hypertension was 12.5% (men 10.9% and women 13.9%). Many risk factors underlying hypertension have been identified including non- modifiable factors such as age, gender, genetic factors, and race, as well as modifiable factors including overweight, high sodium intake, and reduced physical activity. The aim of this review was to present the scenery of hypertension and as well as present the exponential trend of hypertension in Bangladesh. We included 9 studies for the review that met the inclusion criteria and study objectives. Analyses of exponential trend reveled an increase in hypertension prevalence among adult population at a rate of 0.04 (R=0.33) per year. This review studies have demonstrated that interventions aimed at changing these modifiable factors might contribute to prevent the development of hypertension.Cardiovasc. j. 2015; 8(1): 59-64